Gender difference in the use of coronary interventions for patients with acute coronary syndrome: Experience from a major metropolitan hospital in Melbourne, Australia. Issue 1 (January 2017) - Worrall-Carter, Linda; MacIsaac, Andrew; Scruth, Elizabeth; Rahman, Muhammad Aziz
Abstract: Background: Literature suggests an ongoing gender disparity in the use of coronary angiography and subsequent interventions among patients with acute coronary syndrome (ACS). Objectives: The study aimed to examine gender differences in the use of coronary interventions amongst patients with acute coronary syndrome (ACS) admitted to a major metropolitan hospital in Melbourne during the period 2009–2012. Methods: We undertook a retrospective analysis of a hospital database of 2096 ACS patients. ACS included unstable angina (UA), ST-segment-elevation myocardial infarction (STEMI) and non-STEMI (NSTEMI). Results: The mean age of the patients was 64.3 years and 624 (30%) were women. Half of them were diagnosed as NSTEMI, 23% as STEMI and 25% as UA. Compared to men, women were older at admission, less likely to be diagnosed with STEMI and less likely to smoke. No gender difference was observed for severe co-morbidities or use of coronary angiography. Women diagnosed with STEMI were 39% less likely to receive an angioplasty stent (adjusted odds ratio 0.61, 95% confidence intervals 0.39–0.96) and 66% less likely to receive grafts (adjusted OR 0.34, 95% CIs 0.13–0.93). Women diagnosed with NSTEMI were 44% less likely to receive grafts (adjusted OR 0.56, 95% CIs 0.37–0.83). Younger women aged 35–49 years were less likely to receive an angioplasty stent, and older women >50 years were less likely to receive grafts. Conclusions: Adherence to guideline based treatment will help to ensure knowledge translation from guideline to practice. Further research investigating symptom presentation, use of non-invasive tests and medical management of ACS by gender may further explain gender difference for coronary interventions.